Interference of Salivary immunoglobulin A antibodies and other salivary fractions with adherence of Streptococcus mutans to hydroxyapatite. - Gahnberg, L (1982)
The adherence of Streptococcus mutans to hydroxyapatite was studied in the presence of salivary fractions with varying activity of naturally occurring immunoglobulin A (IgA) antibodies. Human parotid saliva from different donors was fractionated by chromatography and compared. Salivary IgA antibodies had no decisive effect on the adherence of the S. mutans strain used. High-molecular-weight salivary components from some subjects had an adherence-promoting effect, whereas fractions collected after the void volume of a Sepharose 2B column always inhibited adherence. The data indicate that the influence of unfractionated saliva on adherence is dependent on the net effect of adherence-promoting and adherence-inhibiting components. This principle has to be considered when the effect of human saliva on microbial adherence is studied.